Ferdinand and the bullies - Walt Disney (Winter Park, FL Advance Publishers, Inc., 1986)
Ferdinand the bull did not like to fight in the bullring
D., 11/12/05, R Madore
Keywords: Ferdinand; Bulls; Juvenile Fiction